MRelief: parche de liberación controlada para el alivio de ardores pericraneales y perivertebralas en pacientes con cefalea crónica tipo tensión (2024)
Chronic tension-type headache (CTTH) is a condition where, in addition to experiencing persistent headaches (more than 15 days per month), individuals suffer from burning sensations in the upper back due to nervous and muscular alterations. This particular symptom reduces the quality of life as it causes difficulty in performing daily activities due to reduced mobility and decreased sleep hours. Moreover, it is a symptom that lacks treatment; analgesics are usually prescribed, but they are often ineffective due to the neurological nature of this symptom. Seeking to provide a specific solution for this symptom and improve the quality of life for patients suffering from CTTH, MRelief was created. These are controlled-release menthol patches designed to help alleviate the burning sensation in the neck and upper back for extended periods. Menthol, as the active compound in the patch, activates the skin's cold receptors, counteracting the burning sensation without lowering body temperature, even with controlled release ensuring a continuous effect for several hours.